Evaluating social learning in England flood risk management: An 'individual-community interaction' perspective. Issue 55 (January 2016) - Benson, David; Lorenzoni, Irene; Cook, Hadrian
Abstract: Stakeholder participation in environmental management has become widespread globally while the normative benefits of multi-stakeholder processes in governing natural resources are promoted by academics and policy makers. As projections indicate more frequent and intense flood events with future climate change, this article examines one stakeholder participation process within UK flood risk management to evaluate whether it contributes to enhancing effective engagement, through social learning. Evidence is derived from multiple interviews conducted within the England's Regional Flood and Coastal Committees (RFCCs), which were specifically introduced to better integrate local level interests in regional flood defence decision-making. In testing a modified 'individual-community interaction' learning framework, it is apparent that personal and group learning outcomes were evident to varying degrees, suggesting that stakeholder participation was relatively successful. However, our analysis suggests that flexibility exists within such structures, allowing reflexive reconstitution to further increase social learning. Recommendations for future stakeholder participation are proposed, providing lessons for both UK flood governance and similar flood risk management processes in other countries.